Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 7 - Functions and Graphs - 7.4 The Algebra of Functions - 7.4 Exercise Set - Page 476: 28



Work Step by Step

RECALL: $(G-F)(x) = G(x)-F(x)$ Using the formula above gives: $(G-F)(x) \\= G(x)-F(x) \\=(5-x)-(x^2-2) \\=5-x-x^2-(-2) \\=5-x-x^2+2 \\=-x^2-x+7$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.